Inflammation activation and resolution in human tendon disease. - Dakin, S; Martinez, F; Yapp, C; Wells, G; Oppermann, U; Dean, B; Smith, R; Wheway, K; Watkins, B; Roche, L; Carr, A (American Association for the Advancement of Science, 2015)
Improved understanding of the role of inflammation in tendon disease is required to facilitate therapeutic target discovery. We studied supraspinatus tendons from patients experiencing pain before and after surgical subacromial decompression treatment. Tendons were classified as having early, intermediate, or advanced disease, and inflammation was characterized through activation of pathways mediated by interferon (IFN), nuclear factor κB (NF-κB), glucocorticoid receptor, and signal transducer and activator of transcription 6 (STAT-6). Inflammation signatures revealed expression of genes and proteins induced by IFN and NF-κB in early-stage disease and genes and proteins induced by STAT-6 and glucocorticoid receptor activation in advanced-stage disease. The proresolving proteins FPR2/ALX and ChemR23 were increased in early-stage disease compared to intermediate- to advanced-stage disease. Patients who were pain-free after treatment had tendons with increased expression of CD206 and ALOX15 mRNA compared to tendons from patients who continued to experience pain after treatment, suggesting that these genes and their pathways may moderate tendon pain. Stromal cells from diseased tendons cultured in vitro showed increased expression of NF-κB and IFN target genes after treatment with lipopolysaccharide or IFNγ compared to stromal cells derived from healthy tendons. We identified 15-epi lipoxin A4, a stable lipoxin isoform derived from aspirin treatment, as potentially beneficial in the resolution of tendon inflammation.